Key events in cancer: Dysregulation of SREBPs - Li, Yunkuo; Wu, Shouwang; Zhao, Xiaodong; Hao, Shiming; Li, Faping; Wang, Yuxiong; Liu, Bin; Zhang, Difei; Wang, Yishu; Zhou, Honglan (Frontiers in Pharmacology, 2023)
Lipid metabolism reprogramming is an important hallmark of tumor progression. Cancer cells require high levels of lipid synthesis and uptake not only to support their continued replication, invasion, metastasis, and survival but also to participate in the formation of biological membranes and signaling molecules. Sterol regulatory element binding proteins (SREBPs) are core transcription factors that control lipid metabolism and the expression of important genes for lipid synthesis and uptake. A growing number of studies have shown that SREBPs are significantly upregulated in human cancers and serve as intermediaries providing a mechanistic link between lipid metabolism reprogramming and malignancy. Different subcellular localizations, including endoplasmic reticulum, Golgi, and nucleus, play an indispensable role in regulating the cleavage maturation and activity of SREBPs. In this review, we focus on the relationship between aberrant regulation of SREBPs activity in three organelles and tumor progression. Because blocking the regulation of lipid synthesis by SREBPs has gradually become an important part of tumor therapy, this review also summarizes and analyzes several current mainstream strategies.